Assessment of molecular and genetic evolution, antigenicity and virulence properties during the persistence of the infectious bronchitis virus in broiler breeders - Fernando, Filipe Santos [UNESP]; Kasmanas, Thaiane Coelho [UNESP]; Lopes, Priscila Diniz [UNESP]; Montassier, Maria de Fátima da Silva [UNESP]; Mores, Marcos Antônio Zanella; Mariguela, Viviane Casagrande [UNESP]; Pavani, Caren [UNESP]; dos Santos, Romeu Moreira [UNESP]; Assayag, Mário Sérgio [UNESP]; Montassier, Helio José [UNESP] (Microbiology Society, 2017)
The infectious bronchitis virus (IBV) causes a highly contagious disease [infectious bronchitis (IB)] that results in substantial economic losses to the poultry industry worldwide. We conducted a molecular and phylogenetic analysis of the S1 gene of Brazilian (BR) IBV isolates from a routinely vaccinated commercial flock of broiler breeders, obtained from clinical IB episodes that occurred in 24-, 46- and 62-week-old chickens. We also characterized the antigenicity, pathogenesis, tissue tropism and spreading of three IBV isolates by experimental infection of specific pathogen-free (SPF) chickens and contact sentinel birds. The results reveal that the three IBV isolates mainly exhibited mutations in the hypervariable regions (HVRs) of the S1 gene and protein, but were phylogenetically and serologically closely related, belonging to lineage 11 of the GI genotype, the former BR genotype I. All three isolates caused persistent infection in broiler breeders reared in the field, despite high systemic anti-IBV antibody titres, and exhibited tropism and pathogenicity for the trachea and kidney after experimental infection in SPF chickens and contact birds. In conclusion, BR genotype I isolates of IBV evolve continuously during the productive cycle of persistently infected broiler breeders, causing outbreaks that are not impaired by the current vaccination programme with Massachusetts vaccine strains. In addition, the genetic alterations in the S1 gene of these isolates were not able to change their tissue tropism and pathogenicity, but did seem to negatively influence the effectiveness of the host immune responses against these viruses, and favour viral persistence.
Keywords: Brazilian genotype; Chicken; IBV; Pathogenicity; Persistence